2021
DOI: 10.1590/fst.04520
|View full text |Cite
|
Sign up to set email alerts
|

Hydration level significantly impacts the freezable - and unfreezable -water contents of native and modified starches

Abstract: The freezable-and unfreezable-water contents of corn and waxy corn starches (native, pregelatinized and retrograded) were analyzed at various hydration levels (25, 35, 45, 55, 65, 75, 85%) using Differential Scanning Calorimetry (DSC). The unfreezable water contents and also the temperature of onset (To), peak (Tp) and endset (Te) of the peaks' in all samples were increased with increasing hydration level. Water absorption index (WAI) and water solubility index (WSI) values of the pregelatinized and retrograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…WSI and WAI of the starches were determined by following Gerçekaslan [ 17 ] with slight modification. One gram (W1) of starch was transferred in a pre-weighed 50 ml falcon tube (W2) and 30 ml of distilled water was added to form a suspension.…”
Section: Methodsmentioning
confidence: 99%
“…WSI and WAI of the starches were determined by following Gerçekaslan [ 17 ] with slight modification. One gram (W1) of starch was transferred in a pre-weighed 50 ml falcon tube (W2) and 30 ml of distilled water was added to form a suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Water has been used as a plasticizer to make modified starches due to its ability to insert into the hydrogen bonds network of starch [42][43][44][45]. It is however unclear how water interacts with the starch in the case of PVA/Starch (hydrated) when from 9:1 to 8:2, a decrease in tensile strength was observed but the opposite effect was seen from 8:2 to 6:4.…”
Section: Preparations and Tensile Test Of Composite Filmsmentioning
confidence: 99%
“…Through the comparison of the setback viscosity of starch, we found that freezing would increase the setback viscosity of starch. The retrogradation of starch causes the aging of foods with high (Gerçekaslan, 2021). Freezable water content is a key factor affecting the nucleation, size and distribution of ice crystals (Ding et al, 2015).…”
Section: Pasting Characteristics Of Starchmentioning
confidence: 99%